2020
DOI: 10.1109/access.2019.2963053
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Methodology for Diagnosing Chronic Kidney Disease

Abstract: Chronic kidney disease (CKD) is a global health problem with high morbidity and mortality rate, and it induces other diseases. Since there are no obvious symptoms during the early stages of CKD, patients often fail to notice the disease. Early detection of CKD enables patients to receive timely treatment to ameliorate the progression of this disease. Machine learning models can effectively aid clinicians achieve this goal due to their fast and accurate recognition performance. In this study, we propose a machi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
107
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 226 publications
(109 citation statements)
references
References 35 publications
0
107
0
2
Order By: Relevance
“…The resultant model achieved a slightly higher predictive accuracy than that of the individual models of RF and LG. It can be observed that decision treebased ensemble modeling approaches consistently produce models with high predictive accuracy for the CKD problem as reported in [10], [12].…”
Section: Related Workmentioning
confidence: 68%
See 4 more Smart Citations
“…The resultant model achieved a slightly higher predictive accuracy than that of the individual models of RF and LG. It can be observed that decision treebased ensemble modeling approaches consistently produce models with high predictive accuracy for the CKD problem as reported in [10], [12].…”
Section: Related Workmentioning
confidence: 68%
“…In this regard, the selected problem is of high interest as it blights the developing countries over a long period. As machine learning-based screening and diagnosis applications provide a workable solution to the many problems faced by the healthcare sector, therefore, recently a lot of scholarly work is reported on developing disease diagnosis and management systems for the CKD [9], [10], [12], [13], [21], [22]. The current study is in the continuation of the scholarly work performed on the CKD diagnosis problem.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations